Asymmetric Hydrogenation on Chirally Modified Pt: Origin of Hydrogen in the N–H–O Interaction between Cinchonidine and Ketone - Maeda, Nobutaka; Hungerbühler, Konrad; Baiker, Alfons (Journal of the American Chemical Society, 2011)
An understanding of the chiral site–substrate interaction is a necessary prerequisite for the rational design and development of efficient heterogeneous asymmetric catalysts. For the enantioselective hydrogenation of α-ketoesters on cinchona-modified platinum, it has earlier been proposed that the crucial interaction is an N–H–O type hydrogen bonding between the quinuclidine N atom of cinchonidine and the α-carbonyl O atom of the substrate. The involved hydrogen atom has been proposed to originate either from protonation (in protic solvent) or from dissociatively adsorbed hydrogen (in aprotic solvent), but experimental evidence for the latter was lacking so far. In this study, in situ attenuated total reflection infrared spectroscopy combined with modulation excitation spectroscopy and phase sensitive detection provides clear evidence that in aprotic media, hydrogen dissociated on Pt is involved in the N–H–O interaction between the chiral modifier, cinchonidine, and the ketone. In the absence of Pt (pure alumina support), no such interaction occurs, indicating the crucial role of dissociated hydrogen in the formation of the diastereomeric transition complex.